Effects of dispersion by Gd3+ upon europium diphenylphosphinate luminescence - Scarpari, S. L.; Stucchi, E. B. (Elsevier B.V., 2001)
A series of binary diphenylphosphinates with Eu3+ and Gd3+ were prepared. The compounds have the general formula Gd1-xEux(DPP)(3), where x ranges from 0 to 1. The spectroscopic measurements show interesting behavior. The intensity of the D-5(0) --> F-7(2) transitions decreases relative to D-5(0) --> F-7(1) With an increase in europium dispersion. Inside the temporal domain, the same decrease is observed with increasing delay after excitation. The lifetimes are also affected, which can be seen in the x = 1 compound, where the decay is a first-order process and lifetime values are 4.81 ms. In the binary compound, as an effect of dispersion, the lifetime of the D-5(0) level measured at the D-5(0) --> F-7(1) transition increases with europium dispersion, and the average along the series is 6.25 ms. The decay measured at the D-5(0) --> F-7(2) transitions reveals a second-order process with lifetimes ranging from 1.90 to 6.00 ms. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: phosphors; chemical synthesis; crystal structure and symmetry; optical properties; luminescence